Personnel : a diagnostic approach - Glueck, William F. (Dallas, Texas : Business Publications, 1978)
The book deals with factors in the individual and in the work environment that influence people at work. Then the challenges of personnel management are discussed- planning for employment, recruitment, selection, etc. This revised edition retains the basic structure and approach of the first edition. The revision discusses the diagnostic factors more fully; each chapter begins with a diagnostic model and an analysis of how the individual and environmental factors affecting the personnel function influence the topic of the chapter.
Includes bibliographical references and index.
ne 12/07/2018
Loans
Keywords: Personnel management